A study on characteristics that affect purchase intention in ecommerce platforms among generation z - Cheong, Xiao Jun (2022)
Digital platforms have become the most popular option to congested malls and inperson shopping as millions of people stayed at home in early 2020 to prevent and control the spread of the virus. In this context, the main objective of this study is to determine the factor affect the purchase intention in e-commerce platforms among Generation Z. With this aim, empirical data were collected with self-administrated questionnaires from 270 convenience sample of consumers who reside in Malaysia and had previously experienced on online shopping. Proposed hypotheses were tested with Statistics Package for Social Sciences (SPSS). In this respect, the Extended Technology Acceptance Model (TAM2) is employed as the theoretical bases to investigate the role trust, subjective norms, perceived ease of use, perceived usefulness, perceived enjoyment affect purchase intention in ecommerce platforms among Generation Z. The findings of this research reported that trust has a positive impact on purchase intention in e-commerce platforms among Generation Z. It was also revealed that subjective norms have a significant relationship between purchase intention in ecommerce platforms among Generation Z. In addition, perceived usefulness was found to have a positive relationship between purchase intention in e-commerce platforms among Generation Z. Moreover, the empirical findings also supported that the impact of trust, subjective norms, and perceived usefulness purchase intention in e-commerce platforms among Generation Z. At the end of this study, theoretical contributions, managerial implications, limitations, and suggestions for future research are discussed.